2016
DOI: 10.3171/2016.5.focus1637
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy versus mini-laparotomy peritoneal catheter insertion of ventriculoperitoneal shunts: a systematic review and meta-analysis

Abstract: OBJECTIVE Ventriculoperitoneal (VP) shunt treatment is the main treatment method for hydrocephalus. The traditional operative approach for peritoneal catheter insertion is mini-laparotomy. In recent years, laparoscopy-assisted insertion has become increasingly popular. It seems likely that use of an endoscope could lower the incidence of shunt malfunction. However, there is no consensus about the benefits of laparoscopy-assisted peritoneal catheter insertion. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…The more minimally invasive technique decreases the length of stay in the hospital as well as prompts a faster recovery rate [9,14]. This allows for less resource use by individual patients and increased patient satisfaction by leaving the hospital soon after surgery and returning to regular activities faster than with the mini-laparotomy technique [9,11,14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The more minimally invasive technique decreases the length of stay in the hospital as well as prompts a faster recovery rate [9,14]. This allows for less resource use by individual patients and increased patient satisfaction by leaving the hospital soon after surgery and returning to regular activities faster than with the mini-laparotomy technique [9,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, shunts are subject to various infections, the majority arising from normal skin flora and occurring within 30 days of surgery [3]. Current studies suggest an overall infection rate of 8.4% and a shunt failure rate, defined as a catheter-related problem necessitating surgical intervention [9], of 51.4% [10]. It has been shown that patients require 2-3 surgical revisions on average due to shunt failures in the 20 years after the original shunt placement [8], with the majority of shunt revisions occurring in the first 6-12 months [4,8].…”
Section: Ventriculoperitoneal Shuntmentioning
confidence: 99%
See 3 more Smart Citations